2021
DOI: 10.1002/eet.1940
|View full text |Cite
|
Sign up to set email alerts
|

Politics of flood risk management in Switzerland: Political feasibility of instrument mixes

Abstract: Complex environmental problems affect multiple policy sectors, decision-making levels and territories simultaneously and, as such, call for encompassing policy solutions. However, no consensus exists on how encompassing policy solutions are designed. A trade-off persists between single instruments, leading to sectoral "silo" thinking and complex instrument mixes, constituting the risk of not being implemented due to actors' objections. Policy designs, including balanced policy mixes, can fulfil various goals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The Veneto data indicate an overall response that is in contrast to the broad-based response developed by Emilia-Romagna. Veneto appeared to establish a hierarchical order in terms of key objectives and operational measures (Glaus, 2021), focusing on "identifying, confirming and rapidly isolating" (key-objective 2-3) both in terms of public health and health assistance through a greater number of swabs and a better ratio of home-based patient care/hospitalization. The strategy therefore has two characteristics: (1) strict subordination and clear chains of command ranging from the regional control room to the emergency team guaranteeing a straightforward, uniform response in line with a coordination model that had already been tested in ordinary conditions (Takeda and Helms, 2006), (2) it was influenced by Crisanti's expertise (see 2.2), turning into medical priorities in operational measures (Capano and Lippi, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Veneto data indicate an overall response that is in contrast to the broad-based response developed by Emilia-Romagna. Veneto appeared to establish a hierarchical order in terms of key objectives and operational measures (Glaus, 2021), focusing on "identifying, confirming and rapidly isolating" (key-objective 2-3) both in terms of public health and health assistance through a greater number of swabs and a better ratio of home-based patient care/hospitalization. The strategy therefore has two characteristics: (1) strict subordination and clear chains of command ranging from the regional control room to the emergency team guaranteeing a straightforward, uniform response in line with a coordination model that had already been tested in ordinary conditions (Takeda and Helms, 2006), (2) it was influenced by Crisanti's expertise (see 2.2), turning into medical priorities in operational measures (Capano and Lippi, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple key objectives may be (1) conflicting: their trade-off is highlighted by the content of the operational measures (Karafili and Lupu, 2017) (2) hierarchical, mainly characterized by the different numbers of related tools available (3) balanced, depending on both the content and the number of operational measures (Glaus, 2021).…”
Section: Creeping Crisis Emergency Managementmentioning
confidence: 99%
“…However, the academic policy integration literature (Runhaar et al, 2014;Tosun & Lang, 2017) emphasizes the fact that cross-sectoral policy integration constitutes a major challenge to policymaking processes and actors involved therein, as many policy decisions are traditionally made within specific policy sectors and silos. As research on crosscutting issues such as water or climate change has shown (Brandenberger et al, 2022;Glaus, 2021), most actors are still "trapped" in their subsystem or sectoral logic. According to the literature, policy integration often involves at least two phenomena (Tosun & Lang, 2017): procedures and content.…”
Section: Theorymentioning
confidence: 99%
“…This is particularly the case within multilevel systems, where power dynamics operate in multiple directions and which can exhibit substantial variance in the instruments they adopt to tackle similar problems (Matti et al, 2017). This may be due to various factors: for example, municipalities that suffer from resource constraints, operate within a context of restricted autonomy and/or receive limited local support for their policy strategies may be less able to push through potentially controversial initiatives (Glaus, 2021; Lesnikowski et al, 2020). As research on multilevel climate governance has identified (e.g., Kern, 2019), such developments may have contributed towards increasing divergence in local policy mixes, particularly in countries where significant contextual differences exist between different areas.…”
Section: Policy Instruments Policy Mixes and Multilevel Governancementioning
confidence: 99%
“…However, they can be expensive and make it easier to identify ‘winners’ and ‘losers’, which might trigger societal opposition (Kuhlmann & Blum, 2021). Societal interests are less likely to oppose informational instruments, which are relatively easy to introduce because they are cheap and do not involve coercion (Glaus, 2021; Kirschke & Kosow, 2021; Lesnikowski et al, 2020). However, their voluntary nature means they are less likely to result in the level of behavioural change that might be necessary to achieve policy objectives (Niles & Lubell, 2012).…”
Section: A New Framework To Explain the Drivers Of Policy Mixes In Mu...mentioning
confidence: 99%